Desain Dan Konstruksi Rawai Ikan Terbang Yang Dioperasikan Di Perairan Wakatobi - Abdul Latif; Naslina Alimina; Ahmad Mustafa; Muslim Tadjuddah; Abdullah Abdullah; Ermayanti Ishak (Universitas Halu Oleo, 2023)
ABSTRACT The development of flying fish longline fishing gear needs to be based on a study of the construction design. The purpose of this research is to determine the purpose of fishing gear design by fishermen as well as the design and construction of flying fish longlines operated by fishermen in Wakatobi waters. The research was carried out in June 2021 in Mola Bahari Village, South Wangi-wangi District, Wakatobi Regency, South east Sulawesi. The research results show that the aim of designing flying fish longlines in Wakatobi waters is for flying fish that live on the surface in a less dense schooling. Then flying fish long lines are designed to stretch across the surface of the water as wide as the school of flying fish. The bait color and shape are adjusted to the natural food of flying fish and the size of the hook is adjusted to the opening of the flying fish's mouth. The design of the flying fish longline operated in Wakatobi waters consists of a main line, branch line, and buoy line with PVF material numbered 4 to 5. Hooks numbered 18 to 19, silk thread bait and a sign float made from a plastic bottle. The total weight of fishing gear ranges from 0.534 kg to 1.244 kg. The total buoyancy of fishing gear is 31.3 kgf to 31.9 kgf, much higher than the total sinking force which ranges from 0.2 kgf to 0.3 kgf. Keywords : flying fish, Wakatobi waters, longlines ABSTRAK Pengembangan alat tangkap rawai ikan terbang perlu didasari kajian tentang desain konstruksinya. Tujuan dari penelitian ini untuk mengetahui tujuan perancangan alat tangkap oleh nelayan serta desain dan konstruksi rawai ikan terbang yang dioperasikan nelayan di perairan Wakatobi. Penelitian dilaksanakan pada bulan juni 2021 di Desa Mola Bahari Kecamatan Wangi-wangi Selatan Kabupaten Wakatobi, Sulawesi Tenggara. Hasil penelitian menunjukkan bahwa tujuan perancangan rawai ikan terbang di perairan Wakatobi adalah ikan terbang yang hidup di bagian permukaan perairan dalam bentuk kawanan yang tidak terlalu padat. Sehingga rawai ikan terbang didesain agar dapat membentang di permukaan air selebar kawanan ikan terbang. Warna dan bentuk umpan disesuaikan dengan makanan alami ikan terbang dan ukuran mata pancing disesuaikan dengan bukaan mulut ikan terbang. Desain rawai ikan terbang yang dioperasikan di Perairan Wakatobi terdiri atas tali utama, tali cabang, dan tali pelampung dengan bahan PVF bernomor 4 hingga nomor 5. Pancing bernomor 18 hingga nomor 19, umpan benang sutera dan pelampung tanda dari botol plastik. Berat total alat tangkap berkisar antara 0,534 kg hingga 1,244 kg. Total gaya apung alat tangkap adalah 31,3 kgf hingga 31,9 kgf, jauh lebih tinggi daripada total gaya tenggelam yang berkisar antara 0,2 kgf hingga 0,3 kgf. Kata Kunci : ikan terbang, perairan Wakatobi, rawai